2015
DOI: 10.1177/0961203315580871
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of quality of life in patients with antiphospholipid syndrome

Abstract: Compared to the general population, APS patients experienced a lower HRQoL. In these patients, a history of arterial thrombosis significantly impaired HRQoL. Therefore, measurements of HRQoL should be included in APS patient management to assess the burden of the disease from a patient's perspective and to provide patients with the support they need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
1
21
1
2
Order By: Relevance
“…HRQoL is an important outcome in rheumatic diseases. Herein we confirm that HRQoL is impaired in PAPS patients when compared with healthy subjects as reported in Caucasian populations . Furthermore, we found that the deterioration in HRQoL was associated with the use of anticoagulants and accrual damage in the vascular domain.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…HRQoL is an important outcome in rheumatic diseases. Herein we confirm that HRQoL is impaired in PAPS patients when compared with healthy subjects as reported in Caucasian populations . Furthermore, we found that the deterioration in HRQoL was associated with the use of anticoagulants and accrual damage in the vascular domain.…”
Section: Discussionsupporting
confidence: 88%
“…Health‐related quality of life (HRQoL) is therefore an important outcome in these patients. In this regard, three recent studies reported impaired HRQoL in PAPS patients when compared with age‐matched healthy Caucasian populations . Zuily et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study involved 163 women with SLE, the control group consisted of 1,045 people. Similarly Zuily et al [60] found that in the general population, patients with SLE have a lower QOL. In these patients, congested blood was a common finding,, which compromise their QOL.…”
Section: The Study Of Qol In Sle Patientsmentioning
confidence: 81%
“…Zuily et al [60] evaluated the QOL in patients with APS. Researchers have shown that the QOL of patients with APS is lower than in healthy volunteers.…”
Section: The Study Of Qol In Sle Patientsmentioning
confidence: 99%